Application of lactic acid in preservation of Euthynnus lineatus fish/ Saiyidah Nafisah Hashim and Mohd Farid Mohd Khotob - Hashim, Saiyidah Nafisah; Mohd Khotob, Mohd Farid (2023)
This research aims to study the effectiveness of lactic acid solution for inhibiting the growth of bacteria on fish and chicken meat samples. This work used an experimental method with observations on the sample’s physical characteristics and identifying the presence of bacteria on tested samples. Three different preservation techniques were conducted with one negative control. The first technique is treatment with lactic acid, second is boiling and third is combination of boiling with addition of lactic acid. The result showed that the combination of boiling and lactic acid had given the best result in preserving the fish sample at room temperature until day 4. The fish samples did not show any sign of spoil and presence of bacteria. Thus, conclude that the combination of boiling technique and lactic acid can really reduce the number of bacteria and extend the life span of the samples.